Texture analysis as a marker for identifying joint changes in temporomandibular disorders on magnetic resonance imaging - Oliveira, Victoria Geisa Brito de [UNESP]; Araujo, Elaine Cristina de Carvalho Beda Correa de [UNESP]; Costa, André Luiz Ferreira; Moraes, Michelle Bianchi de [UNESP]; Lopes, Sérgio Lucio Pereira de Castro [UNESP] (Editora Cubo, 2024)
Objective: The present investigation aimed to characterize Texture Analysis (TA) parameters of the condylar medullary bone and the superior aspect of the lateral pterygoid muscle (LPM) on Magnetic Resonance Imaging (MRI) for the identification of potential changes in individuals with temporomandibular disorder (TMD). Material and Methods: A total of 40 MRI scans was retrospectively selected, consisting of 20 from patients without temporomandibular joint (TMJ) changes (control group) and 20 from patients diagnosed with TMD (TMD group). All MRI scans adhered to a consistent protocol, utilizing an 8.0 cm diameter bilateral surface coil to capture latero-medial parasagittal images with T2-weighted and Proton Density-weighted (PD), both with the mouth closed and at maximum mouth opening. TA was performed using the MaZda 4.20 software (Institute of Electronics, Technical University of Lodz, Poland). The regions of interest (ROI) were standardized for all evaluated images, and texture parameters were calculated through the gray-level co-occurrence matrix method. TA results underwent comparison using the Mann-Whitney test. Results: There was a statistically significant difference in the Correlation and Moment of Inverse Difference parameters between control and TMD groups, notably evident in PD-weighted images for the region of the condylar medullary bone and the LPM, respectively (p<0.05). Conclusion: Thus, the TA method exhibits promising potential to provide valuable information, enhancing the accuracy of TMD diagnosis and classification.
Análise de textura como marcador para identificação de alterações das articulares por disfunções temporomandibulares em imagens por ressonância magnética
Keywords: Dentistry; Diagnostic imaging; Magnetic resonance imaging; Radiomics; Temporomandibular joint dysfunction syndrome